Power transfer control within the framework of vehicle-to-house technology - Hicham Ben Sassi; Yahia Mazzi; Fatima Errahimi; Najia Es-Sbai (Institute of Advanced Engineering and Science, 2023)
The emerging vehicle-to-grid (V2G) technology has gained a lot of praise in the last few years, following its experimental validation in several countries. As a result, this technology is being investigated for standalone houses under the name of vehicle-to-house (V2H). This latter proposes a two-way power transfer between the electric vehicles and isolated houses relying on renewable sources for power supply. In this paper an implementation of the V2H technology is investigated, using the adaptive backstepping control approach for the bidirectional half-bridge and the integral sliding mode control for the DC-DC converter. The robustness of the controller and its capability to respond to the desired performances were tested using different realistic scenarios. The obtained results yielded, a perfect sinusoidal output voltage with a voltage level of 220 V and a frequency of 50 Hz. This is further been validated by a frequency analysis resulting in a THD of 0.25%.